THE ROLE OF RELIGIOUS EDUCATION AND UTILIZATION DIGITAL TECHNOLOGY FOR IMPROVING THE QUALITY IN SUSTAINABILITY MADRASA - Siskandar Siskandar (JURNAL TARBIYAH, 2020)
This study aims to reveal the role of religious education and the use of digital technology in improving the quality of sustainability Madrasa in Indonesia. The research method used is the study of literature. Previous studies only focused on the challenges and role of Islamic education in the digitalization era. The novelty of the research lies in the collaboration of Islamic education theory and new media theory in particular the use of digital technology in improving the quality of Madrasas sustainability in Indonesia. It is essential to know how contemporary Islamic education and digital technology can be developed as crucial factors in Madrasas' sustainability to face challenges in the current digital Era. The results of the study explained that the strengths, as well as the characteristics possessed by Madrasas, are the values of Islamic religiosity that can create a foundation of good character and behavior for the next generation of the nation. To face competition, improve quality, and survive in the world of education, Madrasas must be able to make the best use of digital technology in Madrasah governance, create digital libraries, improve the performance of teachers who are technology literate, and the application of digital technology in learning practices in Madrasa Ibtidaiyah (MI ), Madrasa Tsanawiyah (MTS), and Madrasa Aliyah (MA).